Relationship Quality Of Health Services With The Level Of Satisfaction Of Hospital Patients - Nuraeni; Aszrul AB; Haerani (Comprehensive Health Care, 2019)
Patient satisfaction is a patient's level of feeling that arises as a result of the performance of health services obtained after the patient compares with what he expected so that patient satisfaction is needed quality service. The purpose of this study is to determine the relationship between the quality of health services and the level of patient satisfaction. This study uses an analytical research design with a cross-sectional approach. The sample in this study were 47 respondents. The study was analyzed using chi-square test results of the study showed that the independent variable that is the perception of the quality of health services consisting of five dimensions has a relationship with patient satisfaction is reliability with p = 0.000, responsiveness with p = 0.000, guarantee with p = 0.002, empathy with p = 0,000 and physical evidence with p = 0,000. The conclusion of this study is the relationship between the quality of service reliability with patient satisfaction, there is a responsive relationship with patient satisfaction, there is a guaranteed relationship with patient satisfaction, there is an empathy relationship with patient satisfaction and there is a relationship of physical evidence with patient satisfaction. The advice is expected to health workers to continue to improve the quality of health services in order to achieve patient satisfaction.